Identificación de alteraciones neurológicas en niños de madres con el diagnóstico de covid19 durante el embarazo: revisión bibliográfica - Cabezas Morejón, Sandy Paola (2025)
Coronavirus disease 2019 (COVID-19) is caused by the SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus 2), this disease affected the community in general, however, pregnancy was a factor that increases the risk of having a severe case of COVID-19. That risk remains higher for at least a month after childbirth and continues to increase if a pregnant person has other health problems related to a serious case of COVID-19. Examples of these health problems include obesity, diabetes, high blood pressure and lung disease. Pregnant women who contracted severe COVID-19 were also more likely to develop other health problems because of COVID-19, such as heart or kidney damage, and blood clots. Moderate to severe symptoms of COVID-19 have also been associated with the high risk of experiencing obstetric and neonatal complications: miscarriage, preterm birth, intrauterine growth restriction, high blood pressure or preeclampsia and admission to the intensive care unit with the need for mechanical ventilation. Maternal death from Covid-19 infection ranked first, displacing other causes such as obstetric bleeding and preeclampsia/eclampsia syndrome associated with the high prevalence of Covid-19 infections in our country, because of the poor efficiency of prevention measures. It is concluded that the maternal-foetal binomial was very vulnerable to this risk and medical units collapsed without providing efficient care to this priority group, prevention measures were required, and economic inequality, access, and capacity of health services as a transcendent factor during the onset of the pandemic.